Eco-friendly synthesis of gold nanoparticles using Equisetum diffusum D. Don. with broad-spectrum antibacterial, anticancer, antidiabetic, and antioxidant potentials - Nasir Assad; Marzia Batool Laila; Muhammad Naeem Ul Hassan; Muhammad Fayyaz ur Rehman; Liaqat Ali; Muhammad Mustaqeem; Barkat Ullah; Muhammad Nauman Khan; Majid Iqbal; Sezai Ercişli; Abdullah A. Alarfaj; Mohammad Javed Ansari; et al. (Scientific Reports)
Abstract The present study reports, the eco-friendly synthesis of gold nanoparticles (AuNPs) using Equisetum diffusum D. Don. extract, a medicinal plant known for its therapeutic properties. Phytochemicals present in the extract served as reducing and stabilizing agents for synthesizing stable AuNPs with an average size range of 68.8 nm. The biosynthesized AuNPs were characterized using UV–vis spectroscopy, FTIR, XRD, SEM, EDX, and dynamic light scattering (DLS) methods, confirming their stability, morphology, and crystalline nature. The green synthesized ED@AuNPs exhibited promising biological activities, including broad-spectrum antibacterial activity against both Gram-positive and Gram-negative bacteria, with inhibition zones from 24 to 37 mm. The anticancer activity was assessed through an MTT assay against hepatic carcinoma (HePG2) cells, revealing dose-dependent cytotoxicity with maximum inhibition at 200 µg/mL (47.62%). Antidiabetic activity was demonstrated by starch hydrolysis and enzyme kinetics, with significant α-amylase inhibitory activity up to 70.85%, comparable to the standard drug Acarbose. Moreover, antioxidant activity was conformed through FRAP and DPPH assays, indicating strong free radical scavenging activity and reducing ability. The study demonstrates the potential of biosynthesized ED@AuNPs as multifunctional agents with applications in biomedicine, particularly in antibacterial, anticancer, antidiabetic, and antioxidant therapies, offering an eco-friendly and sustainable approach for nanoparticle synthesis.